(untitled) (MAUSAM, 2007)
Nature of precipitation – alkaline or acidic – depends upon the concentration of major water soluble inorganic gaseous and soil derived particulates dissolved in it. If concentration of cations is higher than that of anions, the precipitation becomes alkaline and vise-a-versa. pH is the main parameter indicating the nature of precipitation. If pH of the solution is < 5.65, it is acidic and > 5.65, alkaline, in the pH scale ranging between 0 & 14. Difference in the chemical composition of rainwater having pH in the alkaline range and acidic range has been studied in this paper. For this purpose, precipitation chemistry data of Allahabad, Jodhpur, Mohanbari and Nagpur for the period 1988-97 have been considered. APWM & S.D. have been worked out. Precipitation chemistry data considering APWM values in acidic range and in alkaline range have been separated and compared. Coefficients of correlation have been calculated in possible cation-anion combinations. It is seen that the lowest pH values (monthly mean) have been recorded during 1997 – MHB (3.77), NGP (4.12), both in acidic range. % Frequency of occurrences of pH values in acidic range was the highest at Mohanbari (66%) in the study period. Jodhpur recorded all pH values in alkaline range indicating influence of soil derived alkaline particulates. Among cations Ca+² has shown its dominance over all cations. Jodhpur has recorded the highest APWM value of Ca+² (9.27mg/lit) in 1997. Data have also been compared with WMO Laboratory simulated acid rain sample analysis data and other non-departmental data. Results are discussed in the paper.